Adventure and mental health: an ecological perspective - Brymer, Eric; Sharma-Brymer, Vinathe; Willis, Royce; Leach, Matthew (Frontiers in Psychology, 2024)
In this paper, we explore the concept of outdoor adventure in the context of mental health, proposing an ecological perspective to redefine adventure beyond its traditional associations with risk and physical challenge. We critically examine current frameworks and definitions of adventure, which often emphasise specific activities and natural environments yet overlook the individual's experience and potential mental health benefits. From an ecological perspective, we emphasise the dynamic interplay between the individual, the activity, and the environment. This approach, grounded in ecological psychology, considers the multi-dimensional nature of adventure, including social, psychological, physical, and spiritual aspects. The paper challenges the traditional risk-focused view of adventure, advocating for a broader definition that includes diverse experiences and interactions, as well as the transformative potential of adventure in various environments, including urban settings. We highlight the changing demographics and motivations of adventure participants, moving away from the stereotypical young male risk-seeker, to more diverse and inclusive participant profiles. We argue that adventure facilitates the realisation of fundamental human affordances, often untapped in daily life, thereby enhancing mental health and wellbeing. This ecological perspective opens new avenues for understanding the role of adventure in mental health and wellbeing, offering a more comprehensive and inclusive approach to adventure activities as therapeutic interventions. This redefined understanding of adventure emphasises its potential as a powerful tool for enhancing human wellbeing, harmonising the relationship between people, tasks, and the environment, and offering profound implications for mental health contexts.